Dinamika Baper dalam Interaksi Sosial Generasi Zilenial: Studi Sensitivitas Emosi dan Komunikasi - Hia, Elisama; Sirikole , Indra; Hatlan, Ruby (Yayasan Albahriah Jamiah Indonesia, 2025)
The phenomenon of baper (carrying feelings) is increasingly found in the social interactions of the Ziennial generation, especially amidst increased social media use, pressure for digital validation, and high exposure to emotional content. Empirically, this generation shows a tendency towards higher emotional sensitivity compared to previous generations, as evidenced by increased conflict due to miscommunication, social anxiety, emotional withdrawal, and a high reliance on digital responses such as likes and comments. Various field findings and psychological reports also indicate that the 18–35 age group experiences a surge in stress, anxiety, and difficulty regulating emotions, particularly due to rapid but miscontextualized digital interactions. This condition shows that baper is not merely a generational stereotype, but a real psychosocial problem that requires treatment. Departing from this urgency, this study aims to understand the phenomenon of baper as a form of emotional sensitivity in the social interactions of the Ziennial Generation. The study used a qualitative approach through in-depth interviews, non-participatory observation, and open-ended questionnaires with purposively selected participants aged 18–35. The results showed that baper is influenced by family parenting patterns, intensity of social media use, the need for digital validation, and mental health challenges such as anxiety and stress. These findings confirm that emotional outbursts reflect the need for social acceptance and emotional stability shaped by the digital context and contemporary culture. The study concludes that empathetic communication strategies, early mental health education, and strengthening emotional intelligence are necessary to enable the Ziennial generation to build healthy and adaptive social interactions in the digital age.